2016
DOI: 10.1016/j.biomaterials.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of a fish scale-derived artificial cornea: Cytotoxicity, cellular adhesion and phenotype, and in vivo immunogenicity

Abstract: The FSCM allows excellent cell growth, is not immunogenic and is well-tolerated in the cornea, and thus meets the basic criteria to serve as a scaffold to reconstitute the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 38 publications
(50 reference statements)
1
62
0
2
Order By: Relevance
“…45 Manufactured to an appropriate thickness, a transparent stromal scaffold derived from the fish scale was evaluated after intrastromal implantation in rabbit corneas, where it was found that the scaffold could be retained in vivo for one year, maintaining transparency without eliciting an immune response. 46 As the fish scales are mechanically robust, they additionally have the potential to be sutured onto the cornea in cases of perforating trauma. This application was tested using a model of full-thickness perforations in minipig corneas, 47 where the fish scale-derived scaffold was successfully used as an emergency patch graft (termed the 'Biocornea'), to temporarily seal the cornea and maintain the integrity of the anterior chamber and eye globe for up to four days (within which time a suitable donor cornea can be sourced in an emergency trauma situation).…”
Section: Fish Scale-derived Corneamentioning
confidence: 99%
“…45 Manufactured to an appropriate thickness, a transparent stromal scaffold derived from the fish scale was evaluated after intrastromal implantation in rabbit corneas, where it was found that the scaffold could be retained in vivo for one year, maintaining transparency without eliciting an immune response. 46 As the fish scales are mechanically robust, they additionally have the potential to be sutured onto the cornea in cases of perforating trauma. This application was tested using a model of full-thickness perforations in minipig corneas, 47 where the fish scale-derived scaffold was successfully used as an emergency patch graft (termed the 'Biocornea'), to temporarily seal the cornea and maintain the integrity of the anterior chamber and eye globe for up to four days (within which time a suitable donor cornea can be sourced in an emergency trauma situation).…”
Section: Fish Scale-derived Corneamentioning
confidence: 99%
“…Graft vascularization has also been observed for other collagenous scaffolds, and in most cases, the neovascularization receded after complete corneal reconstruction. 20,34,35 A certain degree of temporary reversible vascularity can promote corneal reconstruction and will not induce severe inflammation or rejection.…”
Section: Discussionmentioning
confidence: 99%
“…This was higher than the threshold for cytotoxicity, which has been set at 70% according to the ISO standard (ISO: 10993-5:2009 [9]). 34 The live/dead viability/cytotoxicity kit provides a twocolor fluorescence in cell viability test. 35 Live cells with intracellular esterase activity could converse the non-fluorescent cell-permeant Calcein AM to fluorescent calcein, which show green fluorescence.…”
Section: Nsc Cytotoxicitymentioning
confidence: 99%